(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the effects of Medroxy Progesterone Acetate (Injectable contraceptive) on endometrium (uterus) of adult female albino rats. Study Design: Experimental study. Place and Duration of Study: This study was conducted at animal house of Dow University of Health Sciences (DUHS), The Institute of Basic Medical Sciences (IBMS) and Dow Diagnostic Research and Reference laboratory (DDRRL) from March 2012 to August 2012. Materials and Methods: Seventy two female albino rats were selected randomly which were later divided into three groups, named Group A, Group B and Group C. These groups were then subdivided into three subgroups depending on the duration of treatment. Treatment was given for one, two and three months. Group A (n=24) animals were served as controls. Group B as treated (n= 24) and were given MPA (3mg/ kg) according to body weight of rat. Group C, treated group (n= 24) was given double dose of MPA (6 mg/ kg.). Injections (MPA) were given only once at the commencement of experiment to both treated groups; B and C. After 1, 2 and 3 months, the female albino rats were dissected and the uterus was removed for observation of morphological and histological changes. Hematoxylin and Eosin were used to stain uterine tissues while collagen fibers were stained with Masson’s trichrome. Ocular and stage micrometer were used to notice the histological changes in endometrium. Non-parametric test; Kruskal Wallis and Tukey’s were applied for statistical analysis between the group variables. Results: On comparison of control Group A with the treated group B and C, revealed significant changes. Endometrial thickness was reduced significantly in the treated Group B and Group C (p values <0.005). Histologically significant changes were observed in uterine tissue. Conclusion: MPA was found out to produce marked fibrotic changes and causes decreased thickness of endometrium. The study was aimed to increase public awareness regarding possible adverse effects of contraceptive injections on women’s health; therefore will be valuable for clinical practice